HOW TO OPEN A BUSINESS IN GERMANY - Rashidov, Abror; Kholmirzayev, Nurislom (Science technology&Digital finance, 2023)
This publication examines the procedure for starting a business in Germany, the features of various organizational forms, the specifics of opening a business for foreigners, as well as highlights the issues of business insurance and hiring staff.